Formulation of Nanocrystal Loaded Racecadotril Immediate Release Tablets Using Quality by Design – QBD Approach - Chauhan, Bhupendra; Lata, Kusum; Agnihotri, Jaya; Kumar, Dinesh (Journal of Neonatal Surgery, 2025)
Racecadotril is primarily used to treat diarrhoea which acts as a peripherally acting enkephalinase inhibitor. Racecadotril gets rapidly converted to thiorphan which interacts specifically with active site of enkephalinase to produce potent blockade of enzyme, thereby preventing inactivation of endogenous opioid peptides, resulting in immediate release and enhanced drug release. Racecadotril is low solubility compound and most of the studies were performed to improve the solubility with traditional approach of product development. The present study was aimed to apply Design of Experiments (DoE) in the development and optimization of drug release from Racecadotril nanocrystal loaded immediate release tablets using three factor two level (23) full factorial designs with integrated Quality be Design (QbD) approach. Quality target product profile (QTPP) and Critical quality attributes (CQAs) were designed. Risk assessment was used to identify the Formulation variables impacting CQA dissolution. 23 factorial design in which three variables namely concentration of Pearlitol SD200, Crospovidone XL 10 & Microcrystalline cellulose PH 102 (AVICEL PH 102) were at two levels. The main interactive influences were tested using statistical model. The response surface plots were generated by software for analyzing effect of the independent variables on the response. All the batches were prepared by direct compression. The tablets were evaluated physiochemical parameters. Optimized formulation from DOE is analyse for physiochemical test.